Development and Evaluation of Improved Feeders for Goats Suitable to Stall-fed Management System - Upreti, Chet R; Kuwar, Bahadur S; Panday, Shambhu B (Nepal Agriculture Research Journal, 2010)
Five different types of feeders were designed and tested on goats to find out their effectiveness in reducing feed wastage and cost fabrication. Experiment was conducted at Agriculture Research Station (ARS)-Bandipur for two years. Tested feeders were hexagonal, rectangular, hay rack, chain barrel and conventional wooden Tatnu. Feeders were fabricated using iron bars and woods. They were tested with the adult goats for feed wastage and feed contamination. Experimental feeds were fodders twigs (Tanki), forage (Stylo, Napier), crop residue (straw from black bean) and commercial concentrate. Chain barrel type of feeder was also tested at farmer’s field at Baradi. Rectangular feeders have significantly lower (P<0.01) feed wastage (6.61% for fodders) compared to other tested feeders. The fabrication cost was NRs 3200, 1700, 700, 900, and 150 for hexagonal, rectangular; hay rack, chain barrel and conventional wooden Tatnu respectively. The rectangular feeder is suitable for goats feeding in Tarai and in the hills of Nepal. It has provision for feeding fodders, grasses, crop residues and concentrates together at the same time. Chain barrel type had comparatively higher wastage (10.7% for fodder) than the rectangular but was preferred by the farmers due to its low fabricating cost, portable in size, small space required and easy to handle. Therefore, the rectangular feeder is recommended for middle level farmers and chain barrel for small farmers who rear few goats. Key words: Contamination; cost effective; feed saving; small farmer; stall-feed; suitable feeders DOI: 10.3126/narj.v6i0.3368 Nepal Agriculture Research Journal Vol.6 2005 pp.78-83